Peningkatan numerasi pada anak berbasis petualangan angka ajaib - Rahmawati, Fitri Puji; Hidayati, Yulia Maftuhah; Desstya, Anatri; Hidayat, Muhamad Taufik; Nisa, Choirun; Umam, Muhammad Misbahqul (Nur Science Institute, 2025)
Numeracy literacy is an understanding that includes numbers, mathematical operations, and the use of mathematical concepts to solve problems through reasoning skills. In several KKN (Real Work Lecture) programs, we want to implement a numeracy literacy program for elementary school children in grade 6 in Ngrombo Hamlet. This program is given to elementary school children, specifically those in grade 6, totaling 12 people. The method used for this community service activity includes activity preparation, activity implementation, and activity evaluation. Through several methods of this activity, we have obtained quite satisfactory results, from initially children having difficulty completing daily tasks, especially mathematics subjects, to become more understanding in calculating and reasoning on every problem regarding mathematics. The Magic Number Adventure is a game prop we provide; through this adventure-based game, we teach the concept of fractions through fun interactions. The game-based learning method has proven effective because children are more interested and can learn in a fun way.